My Math Forum Calculating optimal isosceles trapezoid

 Calculus Calculus Math Forum

 March 18th, 2017, 11:46 AM #1 Senior Member   Joined: Jan 2017 From: Toronto Posts: 209 Thanks: 3 Calculating optimal isosceles trapezoid Trough is to be formed by bending up two sides of a long metal rectangle so that the cross-section of the trough is an isosceles trapezoid. If the width of the metal sheet is 2 meters, how should it be bent to maximize the volume of the trough? Answer: The sides and bottom should all be 2/3 meter, and the sides should be bent up at angle pi/3. Any tips would be much appreciated.
March 18th, 2017, 12:58 PM   #2
Math Team

Joined: Jul 2011
From: Texas

Posts: 2,977
Thanks: 1571

$A = \dfrac{h}{2}(b_1+b_2)$

$h = x\sin{\theta}$

$b_1 = 2(1-x)$

$b_2 = 2(1-x) + 2x\cos{\theta}$

I started by setting $\dfrac{\partial A}{\partial x} = 0$, solved for $x$ in terms of $\theta$ ...
$x=\dfrac{1}{2-\cos{\theta}}$.

Set $\dfrac{\partial A}{\partial \theta} = 0$, substituted for $x$, found $\cos{\theta} = \dfrac{1}{2} \implies x = \dfrac{2}{3} \text{ and } \theta = \dfrac{\pi}{3}$

Give it a go ...
Attached Images
 max_trap.jpg (7.5 KB, 2 views)

 March 18th, 2017, 01:07 PM #3 Senior Member   Joined: Jun 2015 From: England Posts: 915 Thanks: 271 These figures will not quite work in real life, however since sheet metalwork requires a bend allowance. This will affect the base dimension slightly. SheetMetal.Me – Bend Allowance
March 18th, 2017, 01:23 PM   #4
Senior Member

Joined: Jan 2017
From: Toronto

Posts: 209
Thanks: 3

Simple and beautiful. I need more practices.

Quote:
 Originally Posted by skeeter $A = \dfrac{h}{2}(b_1+b_2)$ $h = x\sin{\theta}$ $b_1 = 2(1-x)$ $b_2 = 2(1-x) + 2x\cos{\theta}$ I started by setting $\dfrac{\partial A}{\partial x} = 0$, solved for $x$ in terms of $\theta$ ... $x=\dfrac{1}{2-\cos{\theta}}$. Set $\dfrac{\partial A}{\partial \theta} = 0$, substituted for $x$, found $\cos{\theta} = \dfrac{1}{2} \implies x = \dfrac{2}{3} \text{ and } \theta = \dfrac{\pi}{3}$ Give it a go ...

March 19th, 2017, 09:38 AM   #5
Senior Member

Joined: Jan 2017
From: Toronto

Posts: 209
Thanks: 3

Here is my work..

P = 2 - 2x
H = x * cos(θ)
Q = 2x * sin(θ) + P = 2 * xsin(θ) + 2 - 2x

A = 1/2 (P + Q) * H
A = 1/2 * (4 - 4x + 2x * sin(θ)) * x * cos(θ)
A = (2 - 2x + x * sin(θ)) * x * cos(θ)

∂A/∂x = 2 * cos(θ) - 4x * cos(θ) + 2x sin(θ) cos(θ) = 0
∂A/∂θ = -2x * sin(θ) + 2x^2 * sin(θ) + 2x * (cos(θ)^2 - sin(θ)^2) = 0

∂A/∂x = cos(θ) - 2x * cos(θ) + x sin(θ) cos(θ) = 0
∂A/∂θ = -x * sin(θ) + x^2 * sin(θ) + x * cos(θ)^2 - x * sin(θ)^2 = 0

2 unknowns, but with 2 complicated equations...
Any tips to help me moving forward would be much appreciated...
Attached Images
 trapezoid.jpg (4.2 KB, 2 views)

 March 19th, 2017, 10:57 AM #6 Math Team     Joined: Jul 2011 From: Texas Posts: 2,977 Thanks: 1571 $A = \dfrac{x\sin{t}}{2}\bigg[4(1-x)+2x\cos{t}\bigg]$ $A = \sin{t}\bigg[2x-2x^2+x^2\cos{t}\bigg]$ $\dfrac{dA}{dx} = \sin{t}\bigg[2 - 4x + 2x\cos{t}\bigg]$ note $\sin{t} \ne 0$ ... $\sin{t}\bigg[2 - 4x + 2x\cos{t}\bigg] = 0 \implies 2 - 4x + 2x\cos{t} = 0 \implies x = \dfrac{1}{2-\cos{t}}$ $A = \dfrac{x}{2}\bigg[4(1-x)\sin{t} + x \cdot 2\sin{t}\cos{t}\bigg]$ $A = \dfrac{x}{2}\bigg[4(1-x)\sin{t} + x\sin(2t)\bigg]$ $\dfrac{dA}{dt} = \dfrac{x}{2}\bigg[4(1-x)\cos{t} + 2x\cos(2t)\bigg]$ note $x \ne 0$ ... $4(1-x)\cos{t} + 2x\cos(2t) = 0$ $4\cos{t} - 4x\cos{t} + 2x(2\cos^2{t}-1) = 0$ $2\cos{t} - 2x\cos{t} + x(2\cos^2{t}-1) = 0$ substitute $\dfrac{1}{2-\cos{t}}$ for $x$ ... $\dfrac{(2\cos{t})(2-\cos{t})}{2-\cos{t}} - \dfrac{2\cos{t}}{2-\cos{t}} + \dfrac{2\cos^2{t}-1}{2-\cos{t}} = 0$ $4\cos{t}-2\cos^2{t} - 2\cos{t} + 2\cos^2{t}-1 = 0$ $2\cos{t} - 1 = 0 \implies \cos{t} = \dfrac{1}{2} \implies t = \dfrac{\pi}{3}$ $x = \dfrac{1}{2-\cos\left(\frac{\pi}{3}\right)} = \dfrac{2}{3}$
March 19th, 2017, 01:10 PM   #7
Senior Member

Joined: Jan 2017
From: Toronto

Posts: 209
Thanks: 3

You sir are a miracle worker! I finally got the answer.

Quote:
 Originally Posted by skeeter $A = \dfrac{x\sin{t}}{2}\bigg[4(1-x)+2x\cos{t}\bigg]$ $A = \sin{t}\bigg[2x-2x^2+x^2\cos{t}\bigg]$ $\dfrac{dA}{dx} = \sin{t}\bigg[2 - 4x + 2x\cos{t}\bigg]$ note $\sin{t} \ne 0$ ... $\sin{t}\bigg[2 - 4x + 2x\cos{t}\bigg] = 0 \implies 2 - 4x + 2x\cos{t} = 0 \implies x = \dfrac{1}{2-\cos{t}}$ $A = \dfrac{x}{2}\bigg[4(1-x)\sin{t} + x \cdot 2\sin{t}\cos{t}\bigg]$ $A = \dfrac{x}{2}\bigg[4(1-x)\sin{t} + x\sin(2t)\bigg]$ $\dfrac{dA}{dt} = \dfrac{x}{2}\bigg[4(1-x)\cos{t} + 2x\cos(2t)\bigg]$ note $x \ne 0$ ... $4(1-x)\cos{t} + 2x\cos(2t) = 0$ $4\cos{t} - 4x\cos{t} + 2x(2\cos^2{t}-1) = 0$ $2\cos{t} - 2x\cos{t} + x(2\cos^2{t}-1) = 0$ substitute $\dfrac{1}{2-\cos{t}}$ for $x$ ... $\dfrac{(2\cos{t})(2-\cos{t})}{2-\cos{t}} - \dfrac{2\cos{t}}{2-\cos{t}} + \dfrac{2\cos^2{t}-1}{2-\cos{t}} = 0$ $4\cos{t}-2\cos^2{t} - 2\cos{t} + 2\cos^2{t}-1 = 0$ $2\cos{t} - 1 = 0 \implies \cos{t} = \dfrac{1}{2} \implies t = \dfrac{\pi}{3}$ $x = \dfrac{1}{2-\cos\left(\frac{\pi}{3}\right)} = \dfrac{2}{3}$

 December 4th, 2017, 09:52 PM #8 Newbie   Joined: Dec 2017 From: China Posts: 2 Thanks: 0 You can find other explanations in this post: https://machinemfg.com/press-brake-ultimate-guide/ Last edited by skipjack; December 5th, 2017 at 03:16 AM.

 Tags calculating, isosceles, optimal, trapezoid

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post mobel Probability and Statistics 1 May 24th, 2016 09:22 AM get42n8 Algebra 6 January 5th, 2015 11:21 AM kittycub4 Calculus 2 October 21st, 2011 03:55 PM Recipe Algebra 4 March 11th, 2010 07:32 PM dai_lo Calculus 1 February 27th, 2008 11:45 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top